The phenology of seed‐propagated globe artichoke. (9th November 2013) - Virdis, A.; Motzo, R.; Giunta, F.
Abstract The ability of globe artichoke to produce inflorescences (capitula) during the autumn when the market price is highest is lost when plants are propagated from seed, as are most F1 hybrid cultivars. To gain an understanding of the phenology of seed‐propagated globe artichoke, both vernalised and non‐vernalised seedlings grown from open pollinated progeny of 'Spinoso sardo' plants were transplanted into the field at two monthly intervals covering a whole year. Final leaf number and the date of unfolding of each leaf were used to calculate the phyllochrons. The average final leaf number increased from 24 to 88 in response to increasing daylength above an approximately 11 h threshold during the first 30 days after emergence, and this variate explained about 90% of the variation in the thermal time taken to reach the bolting stage. The average phyllochron ranged from 56 to 96°Cd among the six emergence dates and was the major underlying physiological cause of the loss of early flowering shown by seed‐propagated plants. Genotypic variation for phyllochron within an emergence date was strongly associated with variation for the length of the emergence to bolting stage period. The limited effect of vernalisation on development indicated that the late flowering tendency of seed‐propagated plants cannot be attributed to an unfulfilled cold requirement.